PENGARUH BEBERAPA FAKTOR TERHADAP KEPUASAN KERJA KARYAWAN PADA PT. ASAM JAWA MEDAN - Ritonga, Sinar (UNIKA Santo Thomas, 2016)
The research objective was to determine the effect of climate variables organiasi, the behavior of the leadership, motivation, and practice decision-making to terhahap job satisfaction of employees at PT. Asam Jawa Medan. The population in this study were all employees at PT. Asam Jawa field numbered 39 and all members of the sample. The analysis model is a linear regression. The results showed that organiasi climate variables, the behavior of the leadership, motivation, decision making and practice simultaneously and partially have a significant influence on employee job satisfaction at. Asam Jawa Medan